Resilient seed systems for climate change adaptation and sustainable livelihoods in the East Africa sub-region: Report of training workshop, Addis Ababa Ethiopia, 17-21 September 2019 - Recha, Tobias; Halewood, Michael; Fadda, Carlo; Mushita, Andrew; Vernooy, Ronnie; Kidane, Yosef Gebrehawaryat; Otieno, Gloria Atieno (2019)
Bioversity International is implementing a Dutch-supported project entitled: Resilient seed systems for climate change adaptation and sustainable livelihoods in the East Africa sub-region. This work aims to boost timely and affordable access to good-quality seed for a portfolio of crops / varieties for millions of women and men farmers’ and their communities across east Africa. A first project training: i) contextualized farmer varietal selection, ii) provided practical demonstrations of tools for climate-change analysis, iii) introduced policy issues associated with managing crop diversity, iv) outlined characterization and evaluation of genetic resources, and v) articulated associated gender issues, and issues related to disseminating elite materials. The training concluded with a contextualizing field trip. In the workshop evaluation, 98% participants declared their overall satisfaction level to be high (74%) or medium (24%), indicating the training furnished them with good ideas for networking and using the tools and methods they learned about.